Mengembangkan Keterampilan Komunikasi Melalui Model Pembelajaran AKIK untuk Guru PAUD di Kabupaten Katingan - Misnawati Misnawati (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Early Childhood Education (PAUD) is an important foundation in children's development, influencing their cognitive, social, emotional and motoric aspects. To improve the quality of teaching, PAUD teachers must develop effective communication skills. In order to achieve this goal, the Katingan District Education Office held an Integrative Holistic PAUD Technical Guidance event which aims to improve the communication skills of PAUD teachers through the AKIK (Active, Communicative, Interactive and Collaborative) learning model. This research uses a qualitative method with a descriptive approach, collecting data through observation, interviews and questionnaires. The research results showed that PAUD teachers participated more actively during the training, their communication skills improved, and they were able to design learning activities that were more communicative and collaborative. The application of the AKIK model has proven effective in creating an interactive learning environment, increasing teacher confidence in communicating, and strengthening collaboration between teachers.